Epilepsy in China: Factors influencing marriage status and fertility. (October 2019) - Li, Sisi; Chen, Jiani; Abdulaziz, Ammar Taha Abdullah; Liu, Yadong; Wang, Xuran; Lin, Mintao; Qin, Yingjie; Liu, Xu; Zhou, Dong
Highlights: In total, 62.1% patients were married, 45.1% patients had a history of fertility. PWE with early age of seizure onset (<18 years) had lower marriage and fertility rates. Employment status mainly affected the marriage rate in male patients. Age, employment status and age at first seizure onset were independently associated with marriage and fertility. Abstract: Purpose: To investigate the current status of marriage and fertility of patients with epilepsy (PWE) and characterize its influencing factors. Methods: A total of 1, 823 adult patients (males age 22 years or older, females age 20 years or older) were included in this study. Data concerning sociodemographic and clinical characteristics were collected. Descriptive analyses, followed by univariate and multivariate logistic regression analyses were utilized to examine factors associated with marriage and fertility of PWE. Marital status of PWE was compared with Chinese population. Standardized marriage rate (SMR) for age and sex was estimated based on the 2010 sixth national population census. Results: 1, 132 patients (62.1%) were married and 823 (45.1%) had a history of fertility. Patients had lower marriage rates than Chinese population (62.1% vs 78.4%). Patients with adult-onset epilepsy (>18 years) had a significantly higher rate of marriage and fertility (p ＜ 0.001) compared to those with childhood-onset epilepsy (≤18 years). Employed patients had higher marriage rates than unemployed patients (64.9% vs 58.6%, p = 0.006), with only male patients being significantly affected by employment status (p ＜ 0.001). Multiple logistic regression revealed that age, age at first seizure onset, and employment status were related to both marriage and fertility. Conclusion: Epilepsy had negative effects on marriage and fertility status. Marriage and fertility rates were lower in patients with Childhood-onset epilepsy (≤18 years). Furthermore, employment status mainly affected the marriage rate of male patients.